Understanding congruence in person-centred counselling practice: A trainee counsellor’s perspective - Sutanti, Natri (ProGCouns: Journal of Professionals in Guidance and Counseling, 2020)
Congruence is a condition in therapeutic relationship that refers to accurate matching of a person’s experience with awareness. In person-centred counselling, counsellor’s congruence is believed as one of helpful and significant aspects that facilitates clients’ growth in counselling. However, this term is quite difficult to understand as a single condition as it interrelated to the other conditions such as empathy and unconditional positive regard. Understanding congruence theoretically and practically is intriguing as well as challenging especially for a trainee counsellor that is still learning to apply theory on practice. This paper aims to critically explore congruence from person-centred counselling theory and to demonstrate some evidences of the development of congruence in practice based on the author’s counselling practice as a trainee counsellor. There are three main discussions in this paper that is to explain congruence from the theoretical point of view, to understand the relation between congruence and acceptance and to explore congruence in person-centred practice. The exploration found that trainee counsellor’s cultural background including condition of worth and language barrier is one of challenges in experiencing congruence within person-centred counselling practice.